2021
DOI: 10.1007/s00221-021-06224-3
|View full text |Cite
|
Sign up to set email alerts
|

Speech apraxia and oral apraxia: association or dissociation? A multivariate lesion–symptom mapping study in acute stroke patients

Abstract: The anatomical relationship between speech apraxia (SA) and oral apraxia (OA) is still unclear. To shed light on this matter we studied 137 patients with acute ischaemic left-hemisphere stroke and performed support vector regression-based, multivariate lesion–symptom mapping. Thirty-three patients presented with either SA or OA. These two symptoms mostly co-occurred (n = 28), except for few patients with isolated SA (n = 2) or OA (n = 3). All patient with either SA or OA presented with aphasia (p < 0.001) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
3
3
0
Order By: Relevance
“…Consistent with our data, previous studies have revealed that bucco-facial apraxic deficits are associated with lesions in the IFG, the insular region and adjacent subcortical regions ( Alexander et al, 1992 , Conterno et al, 2022 , Maeshima et al, 1997 , Raade et al, 1991 , Scandola et al, 2021 , Tognola and Vignolo, 1980 ). These results align with the here identified lesion correlates for bucco-facial gesture imitation deficits located more anterior than lesions associated with arm/hand imitation deficits.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with our data, previous studies have revealed that bucco-facial apraxic deficits are associated with lesions in the IFG, the insular region and adjacent subcortical regions ( Alexander et al, 1992 , Conterno et al, 2022 , Maeshima et al, 1997 , Raade et al, 1991 , Scandola et al, 2021 , Tognola and Vignolo, 1980 ). These results align with the here identified lesion correlates for bucco-facial gesture imitation deficits located more anterior than lesions associated with arm/hand imitation deficits.…”
Section: Discussionsupporting
confidence: 93%
“…Besides temporo-parietal and frontal lesions, bucco-facial apraxia has been associated with striato-capsular lesions ( Conterno et al, 2022 , Raade et al, 1991 , Schmidt et al, 2022 ), consistent with the here revealed subcortical lesion correlates of bucco-facial gesture imitation deficits (including the basal ganglia).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…4,8,9 When neurodegenerative, NVOA can occur with other features such as apraxia of speech (AOS), aphasia, or ideomotor limb apraxia. 2,4,10 It rarely occurs in isolation, and it usually follows a progressive worsening pattern. 2,4,11,12 Most studies evaluating the associations of NVOA have examined clinical syndromes and, less frequently, pathologic outcomes.…”
Section: Introductionmentioning
confidence: 99%